Perceptions of COVID-19 Spread Factors, Socio-Demographic Influences, and Vaccine Efficacy: Insights from Frontline Health Workers in Bhopal, India - Sahu, Anita; Prasad, Jagdish (International Journal of Statistics in Medical Research, 2026)
Background: As frontline warriors against COVID-19, health workers have gained a significant, unique, and invaluable understanding of the virus through personal experience and various studies over the past five years. These insights can provide a more precise understanding of the factors influencing the spread of COVID-19, as well as socio-demographic factors and vaccine efficacy in the long term. Despite a growing body of pandemic literature, studies that capture healthcare workers’ perceptions of community-level transmission remain scarce, and even fewer examine those perceptions alongside socio-demographic drivers and vaccine performance. Objective: To understand what healthcare workers, think about COVID-19 spread factors, socio-demographic influences, and vaccine efficacy in the community, and to assess the key factors they identify, along with the differences and similarities in their perceptions across professional groups. Materials and Methods: A structured questionnaire comprising 32 questions was administered to 252 health workers in Bhopal, India, including doctors, nurses, laboratory technicians, pharmacists, and ambulance drivers. In this study, a descriptive and comparative analysis is performed to identify factors contributing to the spread of COVID-19, as well as significant differences and similarities in how various professions classified and identified these factors, and the demographic risks associated with them. The analysis also evaluates the long-term effectiveness of vaccines. Data were analyzed using the Borda Count technique to establish rankings, while Kendall’s W was used to quantify the strength of agreement across different medical roles. Results: The study revealed notable variations in how different healthcare professions perceived factors influencing the spread of COVID-19, socio-demographic influences, and vaccine efficacy. Doctors and nurses displayed the closest alignment, while pharmacists, lab technicians, and ambulance drivers offered distinct viewpoints shaped by their roles and exposure levels. Despite these differences, all groups agreed on the major transmission mechanisms, the effectiveness of preventive measures, and the importance of vaccination in reducing severity. Conclusion: Health workers across professions contributed diverse but meaningful perspectives on COVID-19, reflecting their clinical and operational experiences. While some differences emerged, there was shared recognition of the need for public cooperation, early detection, and sustained vaccination efforts. These insights underscore the importance of a multidisciplinary, locally responsive approach to enhancing pandemic preparedness and future public health strategies.